(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides an overview of Cognitive linguistics as a modern linguistic discipline. This thesis examines the theoretical foundations, their core principles, and major concepts that demonstrate the process of approaching with cognitive understanding to languages. The research also sheds light into how cognitive linguistics can be included in contemporary linguistic studies and discovers its applications in the areas such as metaphor theory, categorization, and discourse analysis.